Javanese Sufism Transformed: Sunan Bonang's Influence on Contemporary Spiritual Practices - Aprilia Ningpitasari; Dzaky Aulia Rahman (LP3M KH Yazid Karimullah Institute, 2025)
This study aims to provide a comprehensive description of the development of Sufism in Java, focusing primarily on the role of Sunan Bonang as a central figure in spreading and transforming his teachings from the classical period to modern spiritual practices that continue to this day. The research method used is qualitative-historical with a deep literature study approach, including analysis of classical texts, serat (Javanese manuscripts), local manuscripts, and various historical literatures related to Sufism in the Nusantara region. The main findings reveal that Sunan Bonang not only acted as a disseminator of Sufi teachings through cultural and educational approaches but also that his teachings have continued to undergo adaptation, reinterpretation, and innovation within tariqa communities and contemporary spiritual practices. These teachings manifest in collective dhikr, modern Sufi studies, and cultural traditions that actively reinforce the spirituality of Javanese society. This research makes a significant contribution to understanding the continuity and dynamic changes within the Javanese Sufi tradition, as well as its relevance to character education, popular religious practices, and the strengthening of ethical values in the modern era.